2014
DOI: 10.3126/kumj.v11i1.11015
|View full text |Cite
|
Sign up to set email alerts
|

Benign Sinonasal Masses: A Clinicopathological and Radiological Profile

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Nasal polyps were the commonest non-neoplastic sinonasal masses followed by rhinosporidiosis. This is similar to the study conducted by Nepal et al 6 Most common benign neoplastic lesion was angiofibroma (11.9%), whereas malignant lesions included 9.52% of all nasal masses (75% of squamous cell carcinoma and 25% of adenoid cystic carcinoma). According to the study by Sachan et al, 7 commonest non-neoplastic lesion was also nasal polyps (83%), followed by rhinosporidiosis (2%), angiofibroma being the commonest benign neoplastic lesion (7%), and malignant masses accounting for 5% of the total study subjects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nasal polyps were the commonest non-neoplastic sinonasal masses followed by rhinosporidiosis. This is similar to the study conducted by Nepal et al 6 Most common benign neoplastic lesion was angiofibroma (11.9%), whereas malignant lesions included 9.52% of all nasal masses (75% of squamous cell carcinoma and 25% of adenoid cystic carcinoma). According to the study by Sachan et al, 7 commonest non-neoplastic lesion was also nasal polyps (83%), followed by rhinosporidiosis (2%), angiofibroma being the commonest benign neoplastic lesion (7%), and malignant masses accounting for 5% of the total study subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Male predominance was found in case of both neoplastic and non-neoplastic sinonasal masses, but the difference was less in case of non-neoplastic lesions (non-neoplastic: 16 males, 14 females to neoplastic: 10 males, 2 females). The highest incidence of the sinonasal masses was between 16 and 30 years of age, which is similar to the study result of Nepal et al 6 Contrast-enhanced computed tomography PNS was done in 50% patients, which revealed bony erosion in two cases of angiofibroma and two cases of malignant sinonasal tumors.…”
Section: Discussionsupporting
confidence: 88%
“…They represented 9.5-12.5 % of head and neck and 1 % of all ALMs, respectively [7,8,27]. Only a single case of ALM was identified among 331 consecutive benign sinonasal masses (0.3 %) [42]. Since the first description by Maesaka et al [9], no more than 38 well documented cases have been reported in the English literature, mainly as single case reports .…”
Section: Discussionmentioning
confidence: 99%
“…The maxillary sinus is the most common site of origin, while the most common histological type is squamous cell carcinoma. 19,20 It is rarely encountered before the 4th decade of life. In this study, all the tumours originated in the maxillary sinus except 2 cases, one of which was nasopharyngeal carcinoma extending into sinuses & nasal cavity, eroding the lateral wall of nasal cavity, and another was an olfactory neuroblastoma extending from cribriform plate level to entire nasal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The mainstay of radiologic examination in the tumors of nasal cavity is not only to make a differential diagnosis but also to explore the origin, dimensions, orientation of the mass to the surrounding structures, contours and the contrast enhancement of the tumor. 19 Radiological investigations may also help in understanding the type of pathology, extension of lesion and associated sinus pathology. It is to be used as first line tool for diagnosis of malignant cases where extent of disease is important factor for further management.…”
Section: Discussionmentioning
confidence: 99%